SEASONAL VARIATION OF BIOACTIVE ALKALOID CONTENT IN ACONITUM SPP. FROM MANIPUR, INDIA - YOIRENTOMBA MEETEI SINAM,; G. A. SHANTIBALA DEVI, (The Bioscan, 2011)
Present study was carried out to investigate the seasonal variation in content of bioactive alkaloids including aconitine in different plant parts of two species of Aconitum: A. nagarum and A. elwesii collected from Manipur. The total alkaloid content of these two species was not found to be significantly different. However, thin layer chromatography (TLC) profiling of crude alkaloid extracts from roots and leaves indicated high aconitine content in A. nagarum. Further, alkaloid content was determined in terms of aconitine equivalent (AE mg/g) using highperformance liquid chromatography (HPLC). The results indicated that the crude alkaloid content was found to be significantly higher in roots as compared to leaves in both these species. The biosynthesis of alkaloids including aconitine in root was found to be highest in the month of November in both A. nagarum (6.50 AE mg/ g) and A. elwesii (5.54 AE mg/g), respectively. The alkaloid content of leaves was highest in the month of August, (5.44 and 4.84 AE mg/g in A. nagarum and A. elwesii respectively) which is the pre-flowering season in both these species. However, aconitine content decreases significantly (at 5% level of significance) during October– November in A. nagarum leaves. Such change was not observed in A. elwesii leaves. Present study revealed the species and plant part based biological variation in distribution of bioactive alkaloid including aconitine in Aconitum species of the region.